Quantitative estimate of heat flow from a mid-ocean ridge axial valley, Raven field, Juan de Fuca Ridge: Observations and inferences - Salmi, M S; Johnson, H P; Tivey, M A; Hutnak, M (Journal of Geophysical Research: Solid Earth, 2014)
A systematic heat flow survey using thermal blankets within the Endeavour segment of the Juan de Fuca Ridge axial valley provides quantitative estimates of the magnitude and distribution of conductive heat flow at a mid-ocean ridge, with the goal of testing current models of hydrothermal circulation present within newly formed oceanic crust. Thermal blankets were deployed covering an area of 700 by 450 m in the Raven Hydrothermal vent field area located 400 m north of the Main Endeavour hydrothermal field. A total of 176 successful blanket deployment sites measured heat flow values that ranged from 0 to 31 W m−2. Approximately 53{%} of the sites recorded values lower than 100 mW m−2, suggesting large areas of seawater recharge and advective extraction of lithospheric heat. High heat flow values were concentrated around relatively small “hot spots.” Integration of heat flow values over the Raven survey area gives an estimate of conductive heat output of 0.3 MW, an average of 0.95 W m−2, over the survey area. Fluid circulation cell dimensions and scaling equations allow calculation of a Rayleigh number of approximately 700 in Layer 2A. The close proximity of high and low heat flow areas, coupled with previous estimates of surficial seafloor permeability, argues for the presence of small-scale hydrothermal fluid circulation cells within the high-porosity uppermost crustal layer of the axial seafloor.
Keywords: ROV Jason (Remotely Operated Vehicle)